1986
DOI: 10.1212/wnl.36.7.900
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin

Abstract: Plasma transthyretin (TTR, formerly called prealbumin) is a 55-kd protein that participates in the plasma transport of both thyroxine and retinol (vitamin A). TTR concentrations are disproportionately high in human ventricular CSF, suggesting that TTR is either selectively transported across or synthesized de novo within the blood-CSF barrier. To address this question, we adopted a molecular genetic approach; after isolating a cDNA clone encoding human TTR, we previously demonstrated specific TTR messenger RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
1
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(178 citation statements)
references
References 0 publications
7
167
1
1
Order By: Relevance
“…The researchers reported that the diet among the Ibadan community consists mainly of red palm oil and yams (Hendrie as quoted in The New York Times, February 14, 2001). This diet, high in provitamin A (100, 101), should maximize the levels of retinoid available for adequate storage in target tissues (37) and transport to brain by APOE (53) and other retinoid transporters, e.g., apolipoprotein D (54) and TTR (60). Consistent with this hypothesis, APOE4 is not a risk factor for AD in Ibadan (99).…”
Section: Epidemiologic Findings Relating Retinoid To Admentioning
confidence: 87%
See 1 more Smart Citation
“…The researchers reported that the diet among the Ibadan community consists mainly of red palm oil and yams (Hendrie as quoted in The New York Times, February 14, 2001). This diet, high in provitamin A (100, 101), should maximize the levels of retinoid available for adequate storage in target tissues (37) and transport to brain by APOE (53) and other retinoid transporters, e.g., apolipoprotein D (54) and TTR (60). Consistent with this hypothesis, APOE4 is not a risk factor for AD in Ibadan (99).…”
Section: Epidemiologic Findings Relating Retinoid To Admentioning
confidence: 87%
“…TTR is the major carrier of retinol bound to RBP from liver stores through plasma to target tissues. Both RBP alone and complexed with TTR can transport retinoid across the choroid plexus (4,60). RBP and TTR are produced in the fourth ventricle of the brain and are abundant in cerebrospinal fluid (61).…”
Section: Functions Of Retinoid-related Genesmentioning
confidence: 99%
“…Unlike plasma TTR, which is derived primarily from the liver, brain TTR is exclusively produced, secreted, and regulated by the choroid plexus (13)(14)(15). The importance of TTR in CNS development is evidenced by the fact that it is present in very high concentration during prenatal and early postnatal life (16).…”
Section: Neurotoxicities Due To Altered Barrier Functions: Aluminum Amentioning
confidence: 99%
“…Human transthyretin binds thyroxine about 10 times more strongly than triiodothyronine (for review see Robbins and Edelhoch, 1986). Transthyretin is expressed by cells involved in maintaining protein homeostasis in extracellular compartments, such as the hepatocytes in the liver and the ependymal cells of the choroid plexus (Stauder et al, 1986;Herbert et al, 1986). In evolution, the initiation of transthyretin gene expression in the choroid plexus preceded that in the liver by about 2X10* years .…”
mentioning
confidence: 99%